Parents’ perceptions of sleep problems in children with ADHD when using weighted blankets - Maria Lönn; Lena-Karin Erlandsson; Katarina Aili; Petra Svedberg; Håkan Jarbin; Ingrid Larsson (Scandinavian Journal of Occupational Therapy)
Background Parents’ perceptions of children’s sleep problems when using a weighted blanket could enhance the understanding of challenges faced by families with ADHD and sleep problems. This is in alignment with a client-centred approach. Acknowledging, what parents perceive as a problem in a family context.Aim To explore changes in parents’ perceptions of their children’s sleep problems before and after participation in a sleep intervention with weighted blankets.Methods Children with ADHD (n = 45) aged 6–14 participated in a sleep intervention with weighted blankets. Data-collection (baseline + 16-week) using the Children’s Sleep Habits Questionnaire.Results Common sleep problems, such as bedtime resistance, daytime sleepiness, sleep onset delay, and sleep duration, were reported to have improved in 50–75% of the children after using a weighted blanket, according to their parents. Changes were seen also for the less commonly reported parasomnias and nightly awakenings, and these problems were rarely perceived as persistent.Conclusions Reported improvements covered various sleep domains, though some sleep issues persisted. Future evaluation of the effects of weighted blanket should assess multiple dimensions of sleep, before and after use.Significance The client-centred approach, including parents’ perceptions of children’s sleep problems, is important in the evaluation of weighted blankets for children with ADHD.